Combined assessment of climate change and socio-economic development as drivers of freshwater availability in the south of Portugal - Stigter, Tibor Y. (2019)
A combined assessment of the potential impacts from climate change (CC) and socio-economic development (SED) on water resources is presented for the most important aquifer in the south of Portugal. The goal is to understand how CC and SED affect the currently large pressures from water consuming and contaminating activities, predominantly agriculture. Short-term (2020-2050) and long-term (2070-2100) CC scenarios were developed and used to build aquifer recharge and crop water demand scenarios, using different methods to account for uncertainty. SED scenarios were developed using bottom-up and top-down methods, and discussed at workshops with farmers and institutional stakeholders in the water sector. Groundwater use was quantified for each scenario. Together with the recharge scenarios, these were run through a calibrated groundwater flow model, to study their individual and joint impacts on groundwater levels and discharge rates into a coastal estuary. Recharge scenarios show clear negative long-term trends and short-term increase in temporal variability of recharge, though short-term model uncertainties are higher. SED scenario 1 (SED1), predicting intensification and decline of small farms, considered the most likely by all workshop participants, shows a large drop in agricultural area and water demand. SED2, a most desired scenario by farmers, foresees growth and modernization of agriculture, but proves unsustainable in combination with predicted CC without efficient adaptation measures. The results thus reveal that CC in the region will dynamically interact with economic factors, and going one step beyond, CC could be directly integrated as a constraint in the development of SED scenarios. Exercises involving the integration of CC and SED regionally based scenarios, constructed in both bottom-up and top- down fashion and discussed in participatory contexts are still rarely used for adaptation, and specifically adaptation of agriculture to water scarcity. The joint analysis of CC and SED revealed challenging, as it involved the use of different methods across the border between natural and social sciences. In our view this method contributes in an encouraging manner to a more holistic and transdisciplinary water management, by allowing a more plausible identification of what (and if) adaptation measures are needed.